Change in quality of life and return to work and sports after isolated closing-wedge distal femoral osteotomy - Qian Fang; Dong Wang; Wenzheng Liu; Wei Lin; Guanglin Wang (BMC, 2023)
Abstract Purpose To analyze return to work and sports, and health-related quality of life (HRQoL) after closing-wedge distal femoral osteotomy (CWDFO) for valgus deformity and lateral compartmental osteoarthritis. Methods Thirty-three patients underwent isolated CWDFO in our center between January 2018 and June 2020 were enrolled, of whom 32 and 23 patients were included in the return-to-work and return-to-sports analyses, respectively. Short Form-36 (SF-36), Tegner score, Knee injury and Osteoarthritis Outcome Score (KOOS) and visual analog scale (VAS) pain score were compared preoperatively and postoperatively. And postoperative complications were recorded. Results Overall, 33 patients were contacted at a mean follow-up of 37.94 ± 6.68 months, with a median age of 35 years (range: 26-63 years) at the surgery time. The physical component summary of SF-36 (p < 0.001) increased significantly at 1 year postoperatively. All patients returned to work, including 96.86% who returned to the same level of work in 1.89 ± 0.98 months, and to sports, including 78.26% who returned to the same sport level in 6.50 ± 2.05 months. Rates of returning to work (p = 0.215) and sports (p = 0.165) did not differ with work/sports intensity. Tegner scores (p = 0.025) and VAS pain scores (p < 0.001) decreased, and KOOS (p < 0.001) increased at 1 year postoperatively. Revision/conversion surgery was not required. In all, 30.43% patients reported a subjective decrease in sports ability; 82.61% patients considered their sports ability acceptable. Conclusion Patients returned to work/sports after isolated CWDFO, and had increased HRQoL. Patients playing high-impact sports had lower rates of returning to the same sport level, and may require preoperative counseling. Level of evidence IV, Case series.